A preliminary study on the aerobic heterotrophic bacterial flora in giant freshwater prawn, Macrobrachium rosenbergii, hatcheries in Malaysia - Anderson, I.G.; Nor Shamsudin, Mariana; Nash, G. (Elsevier, 1989)
A study was carried out to establish bacterial counts and the aerobic heterotrophic microflora in Macrobrachium rosenbergii hatcheries and larvae in Malaysia. Physicochemical characteristics, wet preparation pathology, and bacterial counts of larval culture tank water, tank sediment, tank surface, larval prawn surface, and washed larval tissue-slurries were determined for 15 larval cultures in three different hatcheries using a modified static "green water" or recirculating clear water rearing system. Tank water, tank sediment and washed larval tissue-slurry microflora was determined for six larval cultures. Sampled cultures ranged in age from 3 to 29 days. Physicochemical water characteristics fell within expected ranges. Thirteen of the larval cultures showed mild bacterial necrosis lesions at prevalences ranging from 2 to 64% of larvae samples examined. Total viable cell counts ranged from 3.7 × 103 to 5.6 × 106 per ml; 1.4 × 105 to 1.1 × 107 per ml; 2.7 × 103 to 5.1 × 105 per cm2; 1.4 × 101 to 5.7 × 105 per larva; and 0 to 2.0 × 105 per larva for the tank water, tank sediment, tank surface, larval surface and washed larval tissue-slurries respectively. Alcaligenes sp. and Vibrio sp. were the most frequently encountered genera. Alcaligenes sp., Bacillus sp., Plesiomonas sp., and Pasteurella sp. were the most abundant strains (prevalence > 10%) in tank water; Alcaligenes sp., Aeromonas sp., Vibrio sp., Plesiomonas sp., and Pasteurella sp., in tank sediment; and Vibrio sp., Alcaligenes sp., and Acinetobacter sp., in washed larval tissue-slurries.